KEHADIRAN PELUKIS SALIM DALAM SEJARAH SENI LUKIS MODERN INDONESIA - M Agus Burhan (Ars: Jurnal Seni Rupa dan Desain, 2008)
Investigating the socio-cultural background, specifically the contradiction among the ideological influences in Indonesia in the late 1950s, cannot be done without discussing Salim. This painter promoted the aesthetic paradigm of ‘universalism’ that emphasized on the freedom of personal expression. Many facts show that Salim was a painter with a firm personality. He built an intensive social relation with Indonesian national movement figures. His paintings contributed significantly to the development of the art of painting in Indonesia. However, he was stick to his decision to stay in Europe. His major rationale was that Europe was his only chance to develop both as human being and a professional painter. In Europe, he intuitively expressed Indonesian values through visual idioms. Europe acknowledged him as a painter with Eastern spirit, whereas in Indonesia he was considered too western. As the matter of fact, he was a universalist. In the bargaining of the aesthetic paradigm the history of modern visual art in Indonesia, Salim existence has been an inspiration and psychological support for painters who fight for universal humanism in his works. His presence was a true manifestation of the national identity issue in art. It was a reflection of political live tradition that is always a color in the journey of Indonesia modern art and culture. Keywords: modern paintings, nationalism, universalism, identity